Correlation between Mindfulness, Coherence and Wisdom in Sample of Different Age Groups in Adulthood - Svence, Guna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are two different researches has been explain in this article. There is common idea of those two researches (Svence, Mihailova, Bebre, 2014)- does age as correlate statistical significant differ scores of mindfulness, wisdom and coherence.The aim of the first research (Svence, Mihailova, 2014) is to make theoretical and practical analysis of correllations between sense of coherence, mindfulness and wellbeing among 25-45 year old women, as also make qualitative analysis in order to explore one of the sense of coherence categories – meaningfulness. Reserach has shown that there exists positive correlation between wellbeing and sense of coherence and between wellbeing and mindfulness, as aslo it has been shown that higher scores of sense of meaning in life is related to higher scores of wellbeing, yet there are nearly no research where the correlations between mindfulness and sense of coherece and/or meaningfulness would be explored. Yet there are enough research where the realaton of these concepts with other concepts such as self-efficacy, anxiety, stressreactivity is confirmed. Considering the above mentioned it is valuable to explore relations between sense of coherence, mindfulness and wellbeing. Principal question of the research was to investigate if there is an association between sense of coherence, mindfulness and wellbeing, as also to make qualitative and quantitative analysis and acquire the broader understanding of this association. There were 36 participants in the research who were asked to fill three questionnaires via internet and to particiapate in the interview. Quantative methods were used in the research (Fife Facet Mindfulness Questionnaire, Orientation to Life Questionnaire to measure sense of coherence, Scales of Psychological Well-Being), as well as statistical methods (Pearson correlation) and qualitative method (content analysis of narratives). Quantitative analysis confirmed the question of the research, since there were significant positive correlations discovered between all three concepts – sense of coherence, mindfulness and wellbeing. Content analysis of narratives was made and several typical content units were discovered whish are related to age appropriate meaningful life tasks, and to the processes of sense of coherence. Therefore the associatio between meaningfulness and other sense of coherence components was confirmed. There is other research (Svence, Bebre,2014) about wisdom and meaningfulness scores- how they correlates and differes in different age subgroups in adulthood.There are some results show- scores of wisdom and meaningfulness are not significant differ in different age groups- early adulthood (20-35), middle age (40-55) mathematical statistical significant, but differences has been finded about wisdom in early adulthood and middle age – according scores – wisdom is more higher in middle age as in early adulthood.